Interpreting palaeofire evidence from fluvial sediments: a case study from Santa Rosa Island, California, with implications for the Younger Dryas Impact Hypothesis. (19th December 2016) - Scott, Andrew C.; Hardiman, Mark; Pinter, Nicholas; Anderson, R. Scott; Daulton, Tyrone L.; Ejarque, Ana; Finch, Paul; Carter‐champion, Alice
ABSTRACT: Fluvial sequences from the late Pleistocene to the Holocene are exposed in Arlington Canyon, Santa Rosa Island, Northern Channel Islands, California, USA, including one outcrop that features centrally in the controversial hypothesis of an extra‐terrestrial impact at the onset of the Younger Dryas. The fluvial sequence in Arlington Canyon contains a significant quantity and range of organic material, much of which has been charred. The purpose of this study was to systematically describe the key outcrop of the Arlington sequence, provide new radiocarbon age control and analyse organic material in the Arlington sediments within a rigorous palaeobotanical and palaeo‐charcoal context. These analyses provide a test of previous claims for catastrophic impact‐induced fire in Arlington Canyon. Carbonaceous spherular materials were identified as predominantly fungal sclerotia; 'carbon elongates' are predominantly arthropod coprolites, including termite frass. 'Glassy carbon' formed from the precipitation of tars during charcoalification. None of these materials indicate high‐temperature formation or combustion. Charcoal and other materials in Arlington Canyon document widespread and frequent fires both before and after the onset of the Younger Dryas, recording predominantly low‐temperature surface fires. In summary, we find no evidence in Arlington Canyon for an extra‐terrestrial impact or catastrophic impact‐induced fire.